Woman speaking to a group - Unknown:::Creator::::::::::::
Negative shows a woman speaking to a group of men and women in a home-like setting. There are stairs behind her and plaques on the wall under the stairs. One man is holding a drinking glass and there are wine bottles and an ice bucket visible on the right side of the picture.